Evaluating zooplankton species diversity using environmental DNA and bulk-DNA metabarcoding in the Ulleung Basin of the Southeastern Korean Peninsula in the summer - Choi, Jae Ho; Kim, Sung; Kim, Choong-gon (Frontiers in Marine Science, 2024)
Accurately investigating the composition of zooplankton species is crucial for monitoring changes in marine ecosystems and assessing biodiversity. In this study, we utilized bulk DNA and environmental DNA metabarcoding in the Ulleung Basin, known for its high zooplankton species diversity among the seas surrounding the Korean Peninsula. Genomic DNA extracted from samples collected during three summer seasons in the survey area was analyzed using high-throughput sequencing of the cytochrome c oxidase I barcode region. We identified 350 species, which were three to six times more than those identified by traditional morphological methods. Furthermore, we observed significant differences in species composition and diversity between bulk DNA and eDNA samples. Notably, eDNA metabarcoding effectively detected species with high swimming ability and those that were difficult to capture using traditional sampling methods. This study underscores the significant impact of sampling methods on research outcomes in zooplankton species diversity studies and highlights the importance of integrating different sampling techniques. Specifically, it suggests the need for the active adoption of non-invasive methods, such as eDNA metabarcoding, for the comprehensive monitoring of diverse biological groups in marine ecosystems.